Model Integrasi Tiga Pilar : Dalam Optimalisasi Pendidikan Islam Sebagai Agen Moderasi Beragama - Halim Murrahman; Martin Kustanti; Bashori (Yayasan Al-Afif, 2025)
Islamic education is vital in shaping character and promoting religious moderation, with traditional institutions effectively implementing formal curricula (state-of-the-art). However, this effectiveness is eroded by the challenges of digital radicalism and the lack of translation of theory into practical practice. The main gap is the absence of an integrated implementation model that holistically transforms moderation into school culture and into concrete student action, as existing efforts are too school-centered and neglect the role of family/community. This research offers a novelty: the Three-Pillar Integration Model (Tri-Pillar). This model synergizes the Core Curriculum (Cognitive), Co-Curricular Activities (Affective) based on experiential learning, and Community/Family Engagement (Psychomotor). The Tri-Pillar Model is proposed as a solution to create a consistent and supportive learning environment. The potential outcome is a significant improvement in students' Religious Moderation Attitude Index (ISMB), encompassing the dimensions of knowledge, tolerance, and national commitment, providing a practical contribution to sustainable radicalism prevention policies.